SEKOLAH ISLAM TERPADU DENGAN PENDEKATAN ARSITEKTUR ORGANIK DI PERUMAHAN BUKIT AZ-ZIKRA SENTUL - Yumna Kamilia Yasmin; Sumaryoto Sumaryoto; Widi Suroto (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Sekolah Islam Terpadu (SIT) as the manifestation of Islamic education system based on Islamic perspective which combines general education and Islamic education in one single curriculum has been having a significant increase in the number of applicants in the last five years in Kabupaten Bogor, which unfortunately is not followed by the increasing number of facilities to be able to accommodate this growing number of applicants. Therefore, additional SIT facility is needed in Kabupaten Bogor. SIT curriculum can run well if the building is designed by a method that is capable to create a learning atmosphere based on Islamic perspective, which takes natural environment and creatures of Allah as the main source of learning through observation and direct interaction. Organic Architecture-based design method which emphasizes harmony between people, building and the environment is appropriate to be applied to SIT building, since the application allows the intensive interaction between human and nature through the integration between the building and the site. The application of Organic Architecture in the building is planned to be applied through the chosen four design aspects of Organic Architecture, where the design is inspired from nature; emphasizes integration with the surrounding environment; optimizes the potential of nature; and utilizes local materials. This can be realized by the selection of sites with supportive environment potential, emphasis on the integration between the interior and exterior through the space module which underlies the shape and appearance of the building, building mass system, and the selection of materials and structures. Keywords: Environment, Integration, Organic Architecture, Sekolah Islam Terpadu